Behavioral Signs of Cerebral Visual Impairment in Very Low Birth Weight Infants. Issue 2 (3rd April 2021) - Stockall, Nancy; Cole, Corinna Villar; Contreras-Vanegas, Alma
ABSTRACT: In this article, the authors identify possible indicators of cerebral visual impairments (CVI) in young children. Noticing the signs of cerebral visual impairment can assist occupational therapists in the early detection and therapy planning for preschoolers in early intervention programs. Several instructional models are described to meet the individual needs of children with CVI.